The use of polyvinyl alcohol hydrogel implants in the lesser metatarsal heads. Is it safely doable? A cadaveric study. Issue 2 (February 2020) - de Cesar Netto, Cesar; Godoy-Santos, Alexandre Leme; Cabe, Taylor N.; Roberts, Lauren E.; Harnroongroj, Thos; Deland, Jonathan; Drakos, Mark
Highlights: Polyvinyl alcohol hydrogel implants can be used to treat lesser MTPJ arthritis. Available implant sizes do not allow preservation of adequate bone rim. Increased metatarsal head height predicted the use of a larger implant. Medial and lateral aspects of the bone rim were usually the ones to fail. Smaller implant options are needed. Abstract: Background: The use of synthetic polyvinyl alcohol hydrogel (PVAH) implants for treatment of lesser toe metatarsophalangeal joint (MTPJ) arthritis is promising and currently limited by the size of implants available. The primary objective of this cadaveric study was to investigate the maximum drilling size and largest PVAH implant dimension that could be safely introduced while still preserving an intact bone rim of the lesser metatarsal heads. Methods: Height and width of all lesser metatarsals were measured on CT and during anatomic dissection. Sequential reaming of the second to fourth metatarsals was performed. Maximum reaming size, largest implant inserted, and failure of the metatarsal head were recorded. Metatarsal head sizes were compared and a multiple regression analysis evaluated measurements that influenced maximum drilling and implant size. Results: CT and anatomical measurements demonstrated significant correlation (ICC range, 0.–0.85). Mean values for height and width of the metatarsal heads were respectively: second (14.9 mm and 9.9 mm), third (14.8 mm and 8.8 mm), fourth (14.0 mm and 8.7 mm) and fifth (12.3 mm and 9.3 mm). All the second, third and fourth metatarsal heads could be safely drilled up to 7.5 mm, preserving an intact bone rim. At 80% of the time, the heads could be safely drilled up to 8.0 mm. Height of the metatarsal heads was the only factor to significantly influence the size of maximum reaming and implant introduced. In respectively 20%, 40% and 50% of the second, third, and fourth metatarsal heads, neither 8 mm nor 10 mm PVAH implants could be used. Conclusions: Our cadaveric study found that the even though the majority of the lesser metatarsal heads could be safely drilled up to 8 mm, the smallest PVAH implant size currently available in most countries (8 mm) could be inserted in most of the second, but only in about half of the third and fourth metatarsal heads. The remaining bone rim around inserted implants was considerably thin, usually measuring less than 1 mm. In order to optimize the use PVAH in lesser metatarsal heads, smaller implant options are needed.